On Some Aspects of the Philosophical Heritage of Ivan Vuković - Akeksandar Milanković (Etnoantropološki Problemi, 2025)
This paper explores certain characteristics of Ivan Vuković's philosophical work, focusing on formal, methodological, and stylistic aspects across a selection of his texts. The sample of the research consists of seven scholarly papers and two books. The formal properties investigated in Vuković's work include: the application of the comparative method, the affirmation of the free essayistic genre, and the stylistic expression. We start from Schopenhauer's point of view that, in assessing the spiritual value of an author's work, it is not primarily important to know what the author wrote or thought about, but how they thought, with the style reflecting the qualitative properties of thinking. The aim of the paper is to identify key characteristics of Vuković's philosophical legacy and to situate them within a certain theoretical perspective. The examined texts demonstrate that Vuković promoted the use of the comparative method in philosophical research thus fostering a form of comparative philosophical study within our philosophical milieu. Furthermore, Vuković reaffirmed the philosophical essay as a genre which, although it may not fit into academic bibliometrics, promotes the development of free, unfettered philosophical thought, rooted in deeply personal ideas and opinions. Finally, through his writing style and his love for cultivated, precise and restrained linguistic expression, Vuković provided a high aesthetic and qualitative criterion for academic writing. His research interests and topics testify that his philosophical foundations are issues of moral freedom and creative culture. Ultimately, Vuković emerges as a key mediator between intricate philosophical questions and problems, general culture, and everyday language.